Citra Perempuan dalam Novel Tirai Menurun Karya Nurhayati Sri Hardini: Kajian Feminisme Eksistensialisme - Riwu Ratu, Vanti; Nai, Firmina Angela; Jama, Karolus Budiman (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2025)
This thesis is entitled The Image of Women in the Novel Tirai Menurun by Nurhayati Sri Hardini, an Existentialism Feminism Study. The problem discussed in this study is how the image of women played by characters named Kedasih and Sumirat in the novel Tirai Menurun by Nurhayati Sri Hardini is studied from social using the theory of four transcendence according to Beauvoir. This research aims to describe the image of women played by the characters named Kedasih and Sumirat in the novel Tirai Menurun by Nurhayati Sri Hardini which is studied from its social aspects using the theory of four transcendences according to Beauvoir. The method used in this research is the descriptive qualitative method. The object of this research is the characters Kedasih and Sumirat in the novel Tirai Menurun by Nurhayati Sri Hardini. The data source in this research is the novel Tirai Menurun by Nurhayati Sri Hardini published by PT Gramedia, Jakarta in 2010. The data collection technique in this research is the library technique, and the analysis technique goes through several stages, namely (a) re-reading the data collected. (b) classifying the image of women in the novel. (c) analyzing the social image of women by using the theory of existentialism feminism which divides the image of women into 4 transcendences. (d) making conclusions. The theory used in this research is existentialist feminism.